Neurodegenerative VPS41 variants inhibit HOPS function and mTORC1‐dependent TFEB/TFE3 regulation. Issue 5 (14th April 2021) - van der Welle, Reini E N; Jobling, Rebekah; Burns, Christian; Sanza, Paolo; van der Beek, Jan A; Fasano, Alfonso; Chen, Lan; Zwartkruis, Fried J; Zwakenberg, Susan; Griffin, Edward F; ten Brink, Corlinda; Veenendaal, Tineke; et al.
Abstract: Vacuolar protein sorting 41 (VPS41) is as part of the Homotypic fusion and Protein Sorting (HOPS) complex required for lysosomal fusion events and, independent of HOPS, for regulated secretion. Here, we report three patients with compound heterozygous mutations in VPS41 ( VPS41 S285P and VPS41 R662 * ; VPS41 c.1423‐2A>G and VPS41 R662 * ) displaying neurodegeneration with ataxia and dystonia. Cellular consequences were investigated in patient fibroblasts and VPS41 ‐depleted HeLa cells. All mutants prevented formation of a functional HOPS complex, causing delayed lysosomal delivery of endocytic and autophagic cargo. By contrast, VPS41 S285P enabled regulated secretion. Strikingly, loss of VPS41 function caused a cytosolic redistribution of mTORC1, continuous nuclear localization of Transcription Factor E3 (TFE3), enhanced levels of LC3II, and a reduced autophagic response to nutrient starvation. Phosphorylation of mTORC1 substrates S6K1 and 4EBP1 was not affected. In a C . elegans model of Parkinson's disease, co‐expression of VPS41 S285P / VPS41 R662 * abolished the neuroprotective function of VPS41 against α‐synuclein aggregates. We conclude that the VPS41 variants specifically abrogate HOPS function, which interferes with the TFEB/TFE3 axis of mTORC1 signaling, and cause a neurodegenerative disease. Synopsis: Compound heterozygous mutations in VPS41 were identified in patients with a neurodegenerative phenotype with dystonia and cerebellar atrophy. VPS41 variants obstruct the HOPS complex, leading to decreased endocytic and autophagy cargo transfer to lysosomes and inhibition of mTORC1 signaling. VPS41 variants lead to an inhibition of mTORC1‐mediated TFE3/TFEB regulation, whereas S6K1/4EBP1/ULK1 remain unaffected. Depletion of HOPS complex subunits prevents TFE3/TFEB phosphorylation, indicating a regulatory role of the HOPS complex in the TFE3/TFEB axis of mTORC1 signaling. Depletion of VPS41 or other HOPS components results in a constitutive upregulation of autophagy and a failure to respond to nutrient starvation. VPS41 variant S285P blocks HOPS complex formation but allows regulated secretion. VPS41 variants decrease the neuroprotective effect of VPS41 against α‐synuclein overexpression in dopaminergic neurons. Abstract : Compound heterozygous mutations in VPS41 were identified in patients with a neurodegenerative phenotype with dystonia and cerebellar atrophy. VPS41 variants obstruct the HOPS complex, leading to decreased endocytic and autophagy cargo transfer to lysosomes and inhibition of mTORC1 signaling.